2019
DOI: 10.1146/annurev-clinpsy-021815-093423
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation and Psychopathology

Abstract: Mindfulness meditation is increasingly incorporated into mental health interventions, and theoretical concepts associated with it have influenced basic research on psychopathology. Here, we review the current understanding of mindfulness meditation through the lens of clinical neuroscience, outlining the core capacities targeted by mindfulness meditation and mapping them onto cognitive and affective constructs of the Research Domain Criteria matrix proposed by the National Institute of Mental Health. We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
194
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(238 citation statements)
references
References 161 publications
9
194
0
5
Order By: Relevance
“…In this respect, psychedelic therapy may resemble fear exposure treatment in CBT. Similar mechanisms have been proposed to underlie the therapeutic effects of mindfulness, which aims to broadly reduce reactivity to private events and is widely applied as a means of exposure in third-wave CBTs (25,(35)(36)(37). In line with the idea that psychedelic states can resemble the exposurelike quality of exercising mindfulness, psychedelics appear to enhance mindfulness capabilities (77)(78)(79), and mindfulnessrelated practices can enhance positive effects of psychedelics (80).…”
Section: Relaxation Of Avoidance-related Beliefsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this respect, psychedelic therapy may resemble fear exposure treatment in CBT. Similar mechanisms have been proposed to underlie the therapeutic effects of mindfulness, which aims to broadly reduce reactivity to private events and is widely applied as a means of exposure in third-wave CBTs (25,(35)(36)(37). In line with the idea that psychedelic states can resemble the exposurelike quality of exercising mindfulness, psychedelics appear to enhance mindfulness capabilities (77)(78)(79), and mindfulnessrelated practices can enhance positive effects of psychedelics (80).…”
Section: Relaxation Of Avoidance-related Beliefsmentioning
confidence: 82%
“…Acceptancebased CBTs commonly pursue exposure through mindfulnessbased exercises, which resemble classical exposure treatment of anxiety disorders in that a stimulus (in this case private events such as emotions, thoughts, memories, or body sensations) is openly attended to while desisting from avoidant responses (25,27,35). The similarity between mindfulness and other exposure treatments is reflected in that regular mindfulness exercise structurally and functionally affects the same network of brain regions that is also assumed to support fear extinction (36,37), suggesting that this type of "internal" exposure can reduce avoidance via the extinction of threat responses to private events. Note that these events may still be unpleasant or painful even when they are no longer experienced as threatening.…”
Section: Promoting Acceptance In Cognitive Behavioral Therapymentioning
confidence: 99%
“…Mindfulness practices have been shown to help reduce anxiety symptoms, depression symptoms, and sadness, and to be useful for modulating one's motivations and behaviors in a broad sense (Kabat-Zinn, 1982, 1994Brown and Ryan, 2003;Creswell and Lindsay, 2014;Papies et al, 2015). Owing to these benefits, mindfulness-based interventions have emerged in medical settings and such interventions have yielded positive effects on physical and mental health (Creswell, 2017;Wielgosz et al, 2019). Recently, researchers in various areas of psychology, including social psychologists as well as industrial and organizational psychologists, have shown increasing interest in mindfulness and preliminary findings suggesting that it can play an active role in improving interpersonal and work settings (Good et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is substantial evidence supporting the effectiveness of mindfulness training to reduce stress in college students, most reported programs involved traditional types of nonactive meditation processes, such as sitting meditation, yogic breathing techniques, guided visualization, and body scanning for progressive muscle relaxation (Spadaro & Hunker, 2016;Stillwell et al, 2017). While these practices form a central core in many meditation techniques, mindfulness meditation may also be used to engage in and maintain states of emotional equanimity during any activity (Wielgosz et al, 2019). When mindfulness practices are engaged in during activities, or occupations, a phenomenon identified as a flow state may occur.…”
mentioning
confidence: 99%